2016
DOI: 10.1186/s13104-016-2270-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on the knowledge and attitudes on advanced life support among medical students and medical officers in a tertiary care hospital in Sri Lanka

Abstract: BackgroundAdvanced life support (ALS) and cardio pulmonary resuscitation, provided at the right time is essential for improving mortality in medical emergencies. Accurate knowledge and skills on this regard, in all medical personals is an essential part of medical education and it should be up to date with varying protocols. The aim of this study is to assess the knowledge and attitudes among the undergraduate medical students and medical officers in the Teaching Hospital Peradeniya and provide suggestions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…In spite of this lack of knowledge and thus potential proficiency, attitudes towards CPR were generally positive. Similar knowledge deficiencies were reported among doctors and medical students in other LMICs, including South India [11], Sri Lanka [8], Jamaica [7], Nigeria [12], and Ethiopia [10].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In spite of this lack of knowledge and thus potential proficiency, attitudes towards CPR were generally positive. Similar knowledge deficiencies were reported among doctors and medical students in other LMICs, including South India [11], Sri Lanka [8], Jamaica [7], Nigeria [12], and Ethiopia [10].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the inclusion of CPR early in medical curricula is thought to increase medical students' awareness and appreciation of this vital skill [2]. Despite being wellestablished and one of the most effective resuscitative measures for patients in cardiac arrest, lack of knowledge, insufficient training, and inadequate practice of CPR have been documented among medical students and junior doctors in high-income as well as low-and middle-income countries (LMICs) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference between males and females regarding knowledge on CPR (table 3). Similar findings were seen in a study conducted by Ralapanawa DM et al 21 Another study done by Ravari H et al 22 among medical interns showed that males were more educated (p=0.041) than females. On the contrary, proper CPR information was higher among females(87%) than males (61%) in a study done among school students in Riyadh by Alanazi et al 23 .…”
Section: Discussionsupporting
confidence: 87%
“…Our study revealed that there was a significant improvement in terms of knowledge after the course, which supports the need to continue in the present approach to delivery of the course. Reihani et al reported similar results when they trained using simulation based on education for advanced cardiac life support skills (11). However, the issue of decay of knowledge over time when there is no continuity in exposure needs to be addressed (12,22,23).…”
Section: Discussionmentioning
confidence: 91%
“…Studies show that there is a lack of knowledge among students regarding cardiopulmonary resuscitation techniques as recommended by international guidelines (4,10,11). It is imperative that universities take on the role of initiating change in the culture of safety and ingrain awareness that does not change when they join the workforce where the patient safety culture is still not optimal.…”
Section: Discussionmentioning
confidence: 99%